Serendipitous Rediscovery of the Facile Cyclization of Z, Z‐3, 5‐Octadiene‐1, 7‐diyne Derivatives to Afford Stable, Substituted Naphthocyclobutadienes. Issue 6 (23rd January 2019) - Barker, Joshua E.; Kodama, Takuya; Song, Min K.; Frederickson, Conerd K.; Jousselin‐Oba, Tanguy; Zakharov, Lev N.; Marrot, Jérôme; Frigoli, Michel; Johnson, Richard P.; Haley, Michael M.
Abstract: The serendipitous isolation of very small amounts of two naphthocyclobutadiene (NCB) derivatives has led to the computational re‐examination of the electrocyclization of Z, Z ‐3, 5‐octadiene‐1, 7‐diyne as well as the experimental and computational study of diethynylindeno[2, 1‐ a ]fluorene derivatives that contain the 3, 5‐octadiene‐1, 7‐diyne motif as part of a larger π‐framework. In both cases the calculated potential energy surface strongly implicates two successive electrocyclic reactions to afford the antiaromatic products. With the octadienediyne fragment locked in the reactive conformation, the postulated diethynylindeno[2, 1‐ a ]fluorene intermediates afford the NCBs in modest to good yields. X‐ray crystallography of four NCBs as well as NICS‐XY scan calculations show that the paratropic motif is located primarily in the benzocyclobutadiene fragment within the larger π‐scaffold. Abstract : Surprise, surprise : Reduction of diethynylindeno[2, 1‐ a ]fluorenediols with SnCl2 affords naphthocyclobutadiene derivatives. Density functional calculations implicate two successive, symmetry‐allowed electrocyclic reactions within the transient diethynylindeno[2, 1‐ a ]fluorene intermediates to give the antiaromatic products. X‐ray crystallography and NICS‐XY scan calculations show that molecule paratropicity is located primarily in the benzocyclobutadiene unit within the larger π‐framework.